FTX contributes to cell proliferation and migration in lung adenocarcinoma via targeting miR-335-5p/NUCB2 axis - Xiaodong Huo; Huixing Wang; Bin Huo; Lei Wang; Kuo Yang; Jinhuan Wang; Lili Wang; Haitao Wang (Cancer Cell International, 2020)
Abstract Background Extensive studies revealed that long non-coding RNAs (lncRNAs) could act as a regulator in tumors, including lung adenocarcinoma (LUAD). LncRNA FTX transcript, XIST regulator (FTX) has been reported to regulate the biological behaviors of some cancers. Nevertheless, its functional role and molecular mechanism remain obscure in LUAD. Our current study concentrates on exploring the biological function of FTX in LUAD. Methods RT-qPCR was used to test the expression of FTX, miR-335-5p or NUCB2 in LUAD cells. The effect of FTX on LUAD progression was investigated by colony formation, EdU, flow cytometry, TUNEL, transwell and western blot assays. The interaction between microRNA-335-5p (miR-335-5p) and FTX or nucleobindin 2 (NUCB2) was confirmed by luciferase reporter assay. Results RT-qPCR showed that FTX expression was up-regulated in LUAD cell lines. Loss-of-function assay indicated that FTX accelerated cell proliferation, migration and invasion, while inhibited cell apoptosis in LUAD. Besides, miR-335-5p, lowly expressed in LUAD cells, was discovered to be sponged by FTX. Subsequently, NUCB2 was identified as a target gene of miR-335-5p. Additionally, it was confirmed that NUCB2 functioned as an oncogene in LUAD. Rescue assays indicated that LUAD progression inhibited by FTX knockdown could be restored by NUCB2 up-regulation. Conclusion FTX played an oncogenic role in LUAD and contributed to cancer development via targeting miR-335-5p/NUCB2 axis.